Mechanical and physical properties of polylactic acid based composite filament using statistical analysis in fused deposition modelling - Mohamad, Nurul Nadia (2025)
Fused Deposition Modelling (FDM) three-dimensional (3D) printing is one of the most broadly employed technique of small additive manufacturing (AM). FDM gained their popularity rather than other AM processes due to its affordable cost and the simple working principle. FDM can employ various of polymers including polylactic acid (PLA). Nowadays, natural fibre (NF) had been chosen as enhancements in FDM filaments as it exhibit excellent specific properties, low cost, and higher availability. However, the addition of NF modified the properties of polymer, thus the printing process parameter need to be reset. FDM had various of printing process parameter that impacted on the properties of the FDM printed part. This study analyses the effect of printing process parameter setup on the mechanical and physical properties of natural fibre reinforced polymer composite (NFRPC) which are sugar palm fibre (SPF)/PLA and pineapple leaf fibre (PALF)/PLA. The optimum printing process parameter for both SPF/PLA and PALF/PLA composites is determine based on the results on the mechanical and physical properties. The correlation between the printing process parameter with the mechanical and physical properties of the SPF/PLA and PALF/PLA composites was also determine in this study. The fabrication of the composites filament preparation started with the cutting, grinding, and sieving the fibres. Then, the process continues with the mixing the fibres with the PLA. Finally, the composites were crushed and extrude into the composite’s filament before the printing process of the samples for the analysation of mechanical and physical properties. The design of experiment utilised in this study was Taguchi method with three levels of printing process parameter which are layer thickness, printing speed and infill density. The total samples printed for each composites filament are 90 samples. The results shown that for SPF/PLA composites, the optimum printing process parameter are 0.1 mm layer thickness, 25 mm/s printing speed and 100% infill density for the good mechanical and physical qualities. From all the parameters, infill density has a positive linear correlation with all properties and layer thickness has a negative linear correlation with all the properties. Thus, infill density concluded to have the greater impact on the tensile properties than the other parameters with r between 0.703 and 0.773. As for PALF/PLA composites, the optimum printing process parameter are 0.1 mm layer thickness, 25 mm/s printing speed and 100% infill density for the good mechanical and physical attributes. From all the parameters, infill density also had a strong positive linear correlation with tensile properties with value of r between 0.931 and 0.951 and layer thickness had a positive linear correlation with the surface roughness with r value of 0.628. Other parameters had a various correlation with the properties. Therefore, infill density is concluded to have the greater impact on the mechanical properties and layer thickness have the higher impact on the surface roughness properties. In conclusion, both SPF/PLA and PALF/PLA had the same optimum printing process parameter for the good mechanical and physical characteristics. In fact, each of the properties for both materials has a different correlation with printing process parameters.